RELATIONSHIP BETWEEN CDCYNERGY'S SOCIAL MARKETING MODEL WITH INTENTION OF HIV COUNSELING AND TESTING FOR PREGNANT WOMEN IN SURAKARTA INDONESIA - Endang Sutisna Sulaeman; Widana Primaningtyas; Heni Hastuti; Anak Agung Alit Kirti Estuti Narendra Putri; Reni Wijayanti; Yeremia Rante Ada; Abdul Rahman (Universitas Muhamadiyah Surakarta, 2021)
ABSTRACTHIV-AIDS epidemic is still becoming a global public health problem. More than 90% of HIV cases in children caused by transmission from their mother. Recent global efforts have focused on eliminating HIV infection in children through HIV counseling and testing for pregnant women (pregnant women VCT). The CDCynergy's social marketing model is widely used as a guide to conceiving robust social marketing plans. This study aimed to analyze the relationship between 6 dimensions of CDCynergy's social marketing model with the VCT intention of pregnant women. An observational analytic method with a survey approach is chosen for this research and the sample size was 90 pregnant women. Closed questionnaire was used as a research instrument. The results of logistic regression analysis showed that the strength of the relationship between VCT intention of pregnant women with the variable